# SOLUTION: i KNOW THAT THIS IS PROBABLY A SIMPLY ONE BUT iM HAVING A TIME TRYING TO FIGURE HOW TO GET THE CORRECT ANSWER. DMVT math student. SOLVE FOR B: AX+BY=C. how do you get an answe

Algebra ->  Expressions-with-variables -> SOLUTION: i KNOW THAT THIS IS PROBABLY A SIMPLY ONE BUT iM HAVING A TIME TRYING TO FIGURE HOW TO GET THE CORRECT ANSWER. DMVT math student. SOLVE FOR B: AX+BY=C. how do you get an answe      Log On

 Ad: Mathway solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Expressions involving variables, substitution Solvers Lessons Answers archive Quiz In Depth

 Question 55675: i KNOW THAT THIS IS PROBABLY A SIMPLY ONE BUT iM HAVING A TIME TRYING TO FIGURE HOW TO GET THE CORRECT ANSWER. DMVT math student. SOLVE FOR B: AX+BY=C. how do you get an answer from this? Found 2 solutions by tutorcecilia, Edwin McCravy:Answer by tutorcecilia(2152)   (Show Source): You can put this solution on YOUR website!AX+BY=C [Isolate the B] AX-AX+BY=-AX+C BY=-AX+C (1/Y)(BY)=(1/Y)(-AX+C) B=(-AX+C)/Y . Check by plugging [B=-AX+C)/Y] back into the original equation. Answer by Edwin McCravy(9719)   (Show Source): You can put this solution on YOUR website!```i KNOW THAT THIS IS PROBABLY A SIMPLY ONE BUT iM HAVING A TIME TRYING TO FIGURE HOW TO GET THE CORRECT ANSWER. DMVT math student. SOLVE FOR B: AX+BY=C. how do you get an answer from this? AX + BY = C The rules for solving for a letter: 1. Get rid of all terms that DO NOT contain the letter to be solved for on the LEFT, and leave all the terms that contain that letter on the LEFT. 2. Get rid of all terms that DO contain the letter to be solved for on the RIGHT, and leave all the terms that DO NOT contain that letter on the RIGHT. AX + BY = C Get rid of the AX term on the left because it does NOT contain B, and leave the BY because it DOES contain B. To get rid of a term, add its opposite to both sides: AX + BY = C -AX - AX ----------------- BY = C - AX Divide both sides by Y BY C - AX ---- = -------- Y Y Cancel the Y's on the left: 1 BY C - AX ---- = -------- Y Y 1 C - AX B = -------- Y Edwin```